Relationship Between Foreign Direct Investment and Employment in Peru: An Empirical Overview - Quispe Domínguez, Ciro Justino; Rodríguez Abraham, Antonio Rafael (LACCEI, 2025)
The research aimed to determine the relationship between foreign direct investment (FDI) and employment in Peru (2014-2023). A quantitative methodology with non-experimental design and correlational scope was used. The sample included annual data on FDI and formal employment, obtained from the Central Reserve Bank (BCR) and the Ministry of Labor (MTPE). The analysis used Pearson's coefficient, previously validating normality with Shapiro-Wilk. The results showed a high and significant positive evaluation (r=0.815; p=0.004), highlighting the impact of FDI in strategic sectors and the need for equitable public policies.